41. Early morphological abnormalities of myelinated fibers in a rat model of CMT1A. Issue 4 (April 2016) - Nolano, M.; Nobbio, L.; Provitera, V.; Pisciotta, C.; Caporaso, G.; Stancanelli, A.; Visigalli, D.; Capodivento, G.; Manganelli, F.; Schenone, A.; Santoro, L.
Abstract : Abnormalities of internodal and nodal length associated with aspects of axonal degeneration have been described in skin samples of Charcot–Marie–Tooth type 1A (CMT1A) patients. It is not clear how early such abnormalities occur and if they change with aging. To elucidate these aspects we assessed myelinated fiber (MF) density and morphometry in skin samples and in the sciatic nerve of hemizygous CMT1A transgenic rats (Sereda et al., 1996) in an asymptomatic and in a late disease course (22 days and 1 year of age). Specimens were obtained from anterior and posterior foot pads, tail and sciatic nerve of CMT1A rats and wild-type littermates and processed with indirect immunofluorescence technique. Quantitative assessment of MF and measurements of caliber, G-ratio, internodal and nodal length were performed. We observed in both, skin and nerve of young and old CMT rats, in addition to nerve fiber loss, several and frequent morphological abnormalities of MF rarely observed in controls. Interestingly, the nerve fibers loss associated at severe aspects of dysmyelination was very marked in the homozygous rat. Measurements on dermal MF showed values of internode length and caliber with a large variability but significantly lower than in controls while nodal length values were significantly higher.